Extra Physical Activities Positively Affect Balance in Children Aged 5–11 Years - Elif Nur Surucu; Lina Budrienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Extra-physical activities (EPA) are necessary for children because they contribute to the development of motor skills and general development.